Hubungan Kondisi Jamban dan Perilaku Sanitasi Lingkungan terhadap Kejadian Diare di Wilayah Belawan Sicanang - Nanda, Meutia; Yustika, Dilla; Lubis, Alvi Hazri; Maipina, Data Rizqueen; Pralistami, Fitri; Putri, Karina Aulia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Diarrhea is a disease closely related to environmental sanitation conditions, such as inadequate toilets and waste problems. According to the World Health Organization (WHO), about 2.2 million people die from diarrhea, directly related to environmental conditions (sanitation/hygiene) and inadequate water (Moernanto, 2009). The health profile data of the district in North Sumatra in 2018 shows that there were 11,151 cases of diarrhea in all age groups, with service coverage reaching 10,280 cases (92.19%). This research method uses a descriptive quantitative design with a cross-sectional approach, conducted in the Belawan Sicanang area. The research sample size was 69 respondents using non-probability sampling, specifically accidental sampling technique. The results of the SPSS analysis based on the chi-square test with α=5% show that there is a relationship between the location of toilet presence, use of clean water, and behavior of waste disposal to the Final Disposal Site (TPA) with the occurrence of diarrhea in the Belawan Sicanang area, with respective P-values of 0.03, 0.015, and 0.02 (p<0.05).